Challenges of Recruitment and Retention of University Students as Research Participants: Lessons Learned from a Pilot Study. Issue 3 (3rd July 2018) - Khatamian Far, Parisa
ABSTRACT: Recruitment of participants into research studies is a great challenge, in particular among higher education students who frequently receive invitations to participate in research projects led by faculty members or fellow students. Researchers need to be mindful of students' motivations and take into account the contributing factors in recruiting students before formulating a recruitment strategy. The primary focus of this paper is to explore the factors which can have an influence on students' decision to participate in research studies as well as effective strategies for facilitating and improving student recruitment. Moreover, the author provides reflection upon a recruitment process of a pilot study discussing the challenges and barriers she encountered during data collection. The main contribution of this paper is to increase awareness and understanding of the multiple facets of students' recruitment, challenges to recruitment efforts and the solutions developed to address them among researchers who might experience similar problems. It is in particular noteworthy as research papers would rarely provide information on the outcome of recruitment experience and reasons behind the low-response rate and failure in participants' retention.